ASSET BASED COMMUNITY DEVELOPMENT (ABCD) IN OPTIMALIZATION MSME OWNED BY MEMBERS OF PAC ANSHOR AND FATAYAT GOMBONG THROUGH DIGITAL MARKETING TRAINING - Siti Fatimah; M. Avicena Fatkhurrohman Al Hudri; Fenika Yulianti; Hanifatul Lutfiyah; Fatikhaturrohmah; Yuli Oktariyanti; Birrotul Muttaqiyah; Dini Istiqomah; Laely Nur Rohmah; Asis Kainanto; Eris Wijayanti (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
This service aims to provide assistance and training on digital marketing to MSME owned by members of Ansor and Fatayat Gombong through the ABCD approach. The participants of this service were all members of PAC GP Ansor and Fatayat Gombong. This activity uses the Asset Based Community Development (ABCD) approach which focuses on utilizing the assets and potential of MSME owned by members of Ansor and Fatayat Gombong. This activity uses six steps consisting of preparing, discovery, dream, design, define, and destiny. The results of the service show that with this training, MSME owners can find out more about digital marketing strategies and platforms that can be developed for promotion. Some of the platforms that have been tested are using WhatsApp, Facebook, and Tokopedia. So that with digital marketing, the profit and public interest are increasing.